Budaya dan Identitas Lokal: Keberlanjutan Batik Banyuwangi melalui Kolaborasi Perajin di Desa Tampo - Dwi Mayuka Vernita,; Ni Made Wiasti,; Aliffiati, Aliffiati (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Batik is a culturally rich traditional textile art form in Indonesia. In 2009, UNESCO officially recognised batik as a non-material cultural heritage. In the midst of changing times and globalisation trends, batik's role in representing Indonesia's cultural identity has become increasingly important. However, batik artisans in the Tampo area of Banyuwangi face a number of challenges in maintaining this tradition. To overcome these challenges and maintain the sustainability of Banyuwangi batik, an in-depth research is needed. This research aims to identify the challenges by batik artisans in Tampo Village, exploring the strategies they use to support the preservation and development of Banyuwangi batik. This research uses a qualitative approach with data collection that include observation, interviews, literature study. The data obtained will be analysed to identify the patterns and strategies used by batik artisans in Tampo Village. This research will provided in-depth view of the preservation and development of Banyuwangi batik and the efforts of the artisans to keep this cultural tradition alive. From the results of this study, the strategies for handling these obstacles are maintaining product quality, making modern motifs, affordable prices, using social media, and government support.